Digital Humanities and Russian Formalism: Darwinism and Anti-Darwinism in Literary History - Steiner, Petr (Bohemica Olomucensia, 2023)
This paper is addressed Franco Moretti's provocative application of the Darwinian evolutionary model based on the divergence of biological species and their survival through natural selection to literary history. This approach was juxtaposed against the ideas of two leading Russian Formalists, Iurii Tynianov and Roman Jakobson, whose explanation of linguistic/literary change was programmatically anti-Darwinian, making conversion (conceived, though, in a particular way) the cornerstone of their respective historiographies. In doing so, they were reacting to the project of historical poetics advanced by the 19th-century Russian Positivist philologist Aleksandr Veselovskii, whose stated goal was to trace the morphological divergences of texts across time and space. The dichotomy ``conversion-diversion,'' my paper illustrated, is not limited to criticism alone. The same frame of reference was invoked in the late 1950s in a famous dispute between the behavioral psychologist B. F. Skinner and the father of the transformational generative grammar, Noam Chomsky, about language acquisition and subsequently in their heated polemics about the human subject's autonomy triggered by the publication of Skinner's book Beyond Freedom and Dignity (1971).
Keywords: literary history; Darwinism; anti-Darwinism; causality; teleology; digital humanities; Formalism; Chomsky; Jakobson; Moretti; Skinner; Veselovskii; Tynianov